Soil‐induced corrosion of ancient Roman brass – A case study. Issue 2 (13th May 2015) - Papadopoulou, O.; Vassiliou, P.; Grassini, S.; Angelini, E.; Gouda, V.
Abstract : This work focuses on the study of the solid state processes on naturally corroded ancient brass artefact. The object, recovered from burial in the Tiber riverbed in Italy, has been characterised from a morphological, chemical and microstructural point of view. The artefact probably originates from a Roman brass coin or medal and the alloy substrate was identified as a leaded brass (85% copper, 12.8% zinc and 2.2% lead). A combination of XRF, SEM coupled with EDS spot analyses and elemental mapping, Raman spectroscopy and OM observations were employed in order to describe the corrosion processes that created the heterogeneous, multi‐layer corrosion product stratification. The identification of copper sulphide layers and the precipitation of some, rarely reported, basic copper and zinc phosphates are among the most important findings of this work. Two phases of anaerobic and aerobic corrosion emerged from the analyses. The object has undergone dezincification at early stages and decuprification later on. However, the most crucial action was the environmental elements activity, which determined the corrosion rate and the nature of the corrosion product layers. The results are critically discussed and correlated with the environmental conditions of the burial context. The study is supported by an extensive literature review.